Answer:
1.1,2,5,8
2.2,3,4,5
3.-7,10,15
Step-by-step explanation:
hope help
First, we need to solve for the common ratio from the data given by using the equation.
a(n) = a(1) r^(n-1)
15 = -3 r^(2-1)
-5 = r
r = -5
Then, we can find the sum by the expression:
S(n) = a(1) ( 1 - r^n) / 1-r
S(8) = -3 (1 + 5^8) / 1+5
S(8) = -195313
Part A.
Amount of money earned = Regular rate per hour *
Number of working hours
M = 12 x
Part B.
Amount of wages earned = Regular rate per hour *
Maximum number of regular working hours + Overtime rate per hour * Excess
working hours
T = 12 * 30 + 16 * y
T = 360 + 16 y
or
T = 16 y + 360
Part C.
Given T = 408, find y:
408 = 16 y + 360
y = 3 hrs
Therefore the total hours Gary worked that week
is,
<span>x + y = 30 + 3 = 33 hrs </span>
<span>(x = 30 since that is the maximum limit for regular working
hours)</span>
These are two questions and two answers:
Question 1:
<span>A
quadratic equation is shown below: 3x^2 − 15x + 20 = 0 Part A: Describe
the solution(s) to the equation by just determining the radicand. Show
your work.
Answer: </span><span>The negative value of the radicand means that the equation does not have real solutions.
Explanation:
1) With radicand the statement means the disciminant of the quadratic function.
2) The discriminant is: b² - 4ac, where a, b, and c are the coefficients of the quadratic equation: ax² + bx + c
3) Then, for 3x² - 15x + 20, a = 3, b = - 15, and c = 20
and the discriminant (radicand) is: (-15)² - 4(3)(20) = 225 - 240 = - 15.
4) The negative value of the radicand means that the equation does not have real solutions.
Question 2:
Part B: Solve 3x^2 + 5x − 8 = 0 by using an appropriate
method. Show the steps of your work, and explain why you chose the
method used.
Answer: </span> two solutions x = 1 and x = - 8/3x
Explanation:
1) I choose factoring (you may use the quadratic formula if you prefer)
2) Factoring
Given: 3x² + 5x − 8 = 0
Make 5x = 8x - 3x: 3x² + 8x - 3x - 8 = 0
Group: (3x² - 3x) + (8x - 8) = 0
Common factors for each group: 3x(x -1) + 8(x - 1) = 0
Coomon factor x - 1: (x - 1) (3x + 8) = 0
The two solutions are for each factor equal to zero:
x - 1 = 0 ⇒ x = 1
3x + 8 = 0 ⇒ x = -8/3
Those are the two solutions. x = 1 and x = - 8/3